(untitled) (Ius Novum, 2020)
A given state’s membership of the European Union may limit its regulatory discretion and legislative activities. It results from the principle of primacy of the Union law as well as the Treaties-based division of competences between the Union and the Member States. Moreover, there is a series of areas such as public aid, regulations concerning technical norms, rules for the functioning of the internal market or currency policy, which require notification of any national legal acts to the European Commission or the European Central Bank. The Member States, adjusting national law to the Union directives, also act within the limits determined by the objective of a given directive. All those obligations then translate into national legislative processes. In Poland, every legal act adopted by the Sejm is evaluated from the point of view of obligations resulting from the membership of the European Union. The analysed legislative processes in the period connected with the 2015 electoral campaign and the fulfilment of election promises proved that in general the Union law either did not cover the regulatory subject matter or the national legislator, passing legal acts connected with the election promises, ensured respect for the Union law.